2003
DOI: 10.1002/jcc.10223
|View full text |Cite
|
Sign up to set email alerts
|

Structures and energies of D‐galactose and galabiose conformers as calculated by ab initio and semiempirical methods

Abstract: Optimized geometries and total energies of some conformers of alpha- and beta-D-galactose have been calculated using the RHF/6-31G* ab initio method. Vibrational frequencies were computed at the 6-31G* level for the conformers that favor internal hydrogen bonding, in order to evaluate their enthalpies, entropies, Gibbs free energies, and then their structural stabilities. The semiempirical AM1, PM3, MNDO methods have also been performed on the conformers GG, GT, and TG of alpha- and beta-D-galactose. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 55 publications
(33 reference statements)
3
14
1
Order By: Relevance
“…162,163,338 For Man the available quantum-mechanical results 255,337,342 also suggest a counterclockwise network in the lowest-energy conformer, but along with a H 6 !O 4 hydrogen-bond. The same counterclockwise network was also found in previous quantummechanical calculations on Gal or its O 1 -methylated derivative in vacuum, 104,162,163,255,337,340,[343][344][345][346] although most of these calculations (see, however 104,343 ) as well as IR ion-dip experiments on phenyl-b-D D-galactopyranoside in the gas-phase 162,163,344 suggested the presence of a H 6 !O 5 hydrogen-bond (as in Glc) rather than a H 6 !O 4 hydrogen-bond (present simulation) in the lowest-energy conformer. Finally, for Tal, the only quantum-mechanical study available to our knowledge also supports the presence of a H 6 !O 5 hydrogenbond.…”
Section: Intramolecular Hydrogen-bondingsupporting
confidence: 55%
“…162,163,338 For Man the available quantum-mechanical results 255,337,342 also suggest a counterclockwise network in the lowest-energy conformer, but along with a H 6 !O 4 hydrogen-bond. The same counterclockwise network was also found in previous quantummechanical calculations on Gal or its O 1 -methylated derivative in vacuum, 104,162,163,255,337,340,[343][344][345][346] although most of these calculations (see, however 104,343 ) as well as IR ion-dip experiments on phenyl-b-D D-galactopyranoside in the gas-phase 162,163,344 suggested the presence of a H 6 !O 5 hydrogen-bond (as in Glc) rather than a H 6 !O 4 hydrogen-bond (present simulation) in the lowest-energy conformer. Finally, for Tal, the only quantum-mechanical study available to our knowledge also supports the presence of a H 6 !O 5 hydrogenbond.…”
Section: Intramolecular Hydrogen-bondingsupporting
confidence: 55%
“…Furthermore, the lowest energy structure of the Na(β-Glc) + system has the β-glucose in a boat conformation and acting as a tridentate ligand, very similar to the lowest energy β-Glc-B-356 structure found for Li(β-Me-Glc) + . The lowest energy structures calculated by Armentrout and coworkers were consistent with the previous results obtained by Kentäma and coworkers for the arabinose and xylose systems, 26 with Barrows et al 25 for the glucose systems, and Rahal-Sekkal et al 30 for galactose saccharide. However, these results contrast with earlier results from Wesdemiotis and coworkers 31 on sodiated monosaccharide and disaccharide complexes.…”
Section: Figuresupporting
confidence: 87%
“…In a study on a mono-and disaccharide, it was reported that AM1 and HF/6-31G* resulted in similar structural results. 26 Among the methods used in the current Article, B3LYP/6-31G* is the most accurate for the determination of energies, followed by AM1, with much larger errors from the Hartree-Fock calculations. 25 The current study is not intended to be a systematic examination of computational methods, or a documentation of differences between theory and experiment.…”
Section: Methodsmentioning
confidence: 99%